The Effect of Land Area, Labor, Fertilizer Subsidyon Agricultural Production In Indonesia - Pangihutan Syafriansyah Pasaribu; Fitrawaty Fitrawaty; M. Fitri Rahmadana (RIRAI Publisher, 2024)
The problem in this research is the increasingly depleting land area in the agricultural sector that occurred in Indonesia from 2010 to 2020, Employment in the agricultural sector has increased from 2010 to 2020, Instability of Agricultural Fertilizer Subsidies in the agricultural sector that occurred in Indonesia from 2010 to 2020, Production Agriculture for rice, potatoes, tomatoes, eggplant and chilies has increased from 2010 to 2020. The location of this research is in Indonesia. The scope of this research was carried out by focusing on discussing the influence of land area, labor, fertilizer subsidies on agricultural production in Indonesia from 1990-2020. The data analysis technique used in this research refers to the Error Correction Model (ECM) equation model by estimating short-term and long-term relationships between the variables Land Area, Labor, Fertilizer Subsidies and Agricultural Production in Indonesia from 1990-2020.